Welcome to OGeek Q&A Community for programmer and developer-Open, Learning and Share
Welcome To Ask or Share your Answers For Others

Categories

0 votes
958 views
in Technique[技术] by (71.8m points)

haskell - Type of fun g x = ys where ys = [x] ++ filter (curry g x) ys?

I'm trying to understand why the type of fun g x = ys where ys = [x] ++ filter (curry g x) ys is ((a, a) -> Bool) -> a -> [a].

I understand that:

filter :: (a -> Bool) -> [a] -> [a] and that curry :: ((a, b) -> c) -> a -> b -> c

But I don't understand how to continue.

See Question&Answers more detail:os

与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
Welcome To Ask or Share your Answers For Others

1 Reply

0 votes
by (71.8m points)

The approach below is not necessarily the easiest or fastest, but it's relatively systematic.


Strictly speaking, you're looking for the type of

g -> ( x -> let ys = (++) [x] (filter (curry g x) ys) in ys)

(let and where are equivalent, but it's sometimes a little easier to reason using let), given the types

filter :: (a -> Bool) -> [a] -> [a]
curry :: ((a, b) -> c) -> a -> b -> c

Don't forget that you're also using

(++) :: [a] -> [a] -> [a]

Let's first look at the 'deepest' part of the syntax tree:

curry g x

We have g and x, of which we haven't seen before yet, so we'll assume that they have some type:

g :: t1
x :: t2

We also have curry. At every point where these functions occur, the type variables (a, b, c) can be specialized differently, so it's a good idea to replace them with a fresh name every time you use these functions. At this point, curry has the following type:

curry :: ((a1, b1) -> c1) -> a1 -> b1 -> c1

We can then only say curry g x if the following types can be unified:

t1  ~  ((a1, b1) -> c1)       -- because we apply curry to g
t2  ~  a1                     -- because we apply (curry g) to x

It's then also safe to assume that

g :: ((a1, b1) -> c1)
x :: a1
---
curry g x :: b1 -> c1

Let's continue:

filter (curry g x) ys

We see ys for the first time, so let's keep it at ys :: t3 for now. We also have to instantiate filter. So at this point, we know

filter :: (a2 -> Bool) -> [a2] -> [a2]
ys :: t3

Now we must match the types of filter's arguments:

b1 -> c1  ~  a2 -> Bool
t3        ~  [a2]

The first constraint can be broken down to

b1  ~  a2
c1  ~  Bool

We now know the following:

g :: ((a1, a2) -> Bool)
x :: a1
ys :: [a2]
---
filter (curry g x) ys :: [a2]

Let's continue.

(++) [x] (filter (curry g x) ys)

I won't spend too much time on explaining [x] :: [a1], let's see the type of (++):

(++) :: [a3] -> [a3] -> [a3]

We get the following constraints:

[a1]  ~  [a3]           -- [x]
[a2]  ~  [a3]           -- filter (curry g x) ys

Since these constraints can be reduced to

a1  ~  a3
a2  ~  a2

we'll just call all these a's a1:

g :: ((a1, a1) -> Bool)
x :: a1
ys :: [a1]
---
(++) [x] (filter (curry g x) ys) :: [a1]

For now, I'll ignore that ys' type gets generalized, and focus on

x -> let { {- ... -} } in ys

We know what type we need for x, and we know the type of ys, so we now know

g :: ((a1, a1) -> Bool)
ys :: [a1]
---
(x -> let { {- ... -} } in ys) :: a1 -> [a1]

In a similar fashion, we can conclude that

(g -> (x -> let { {- ... -} } in ys)) :: ((a1, a1) -> Bool) -> a1 -> [a1]

At this point, you only have to rename (actually, generalize, because you want to bind it to fun) the type variables and you have your answer.


与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
OGeek|极客中国-欢迎来到极客的世界,一个免费开放的程序员编程交流平台!开放,进步,分享!让技术改变生活,让极客改变未来! Welcome to OGeek Q&A Community for programmer and developer-Open, Learning and Share
Click Here to Ask a Question

...